2013
DOI: 10.1016/s1995-7645(13)60041-3
|View full text |Cite
|
Sign up to set email alerts
|

Casticin induces caspase-mediated apoptosis via activation of mitochondrial pathway and upregulation of DR5 in human lung cancer cells

Abstract: Our results demonstrate that casticin induces caspase-mediated apoptosis via activation of mitochondrial pathway and upregulation of DR5 in human lung cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 29 publications
1
30
0
5
Order By: Relevance
“…The IC 50 value (concentration that result at 50% cell death) of RSV against A549 cells was 8.9±1.3 μM. In this study, it was also shown that RSV significantly activated caspase-3, the crucial mediators of apoptosis (Mcllwain et al, 2013;Zhou et al, 2013), in a dose-dependent manner. It also exhibited a dose-dependent tumour growth inhibition effect.…”
Section: Synergistic Effect Of Resveratrol and Radiotherapy In Controsupporting
confidence: 61%
“…The IC 50 value (concentration that result at 50% cell death) of RSV against A549 cells was 8.9±1.3 μM. In this study, it was also shown that RSV significantly activated caspase-3, the crucial mediators of apoptosis (Mcllwain et al, 2013;Zhou et al, 2013), in a dose-dependent manner. It also exhibited a dose-dependent tumour growth inhibition effect.…”
Section: Synergistic Effect Of Resveratrol and Radiotherapy In Controsupporting
confidence: 61%
“…It is shown that Res could significantly activated Caspase-3 in a dosedependent manner. Caspases are crucial mediators of programmed cell death (apoptosis) (Zhou et al, 2013). As reported, Caspase-3 is a frequently activated death protease, catalyzing the specific cleavage of many key cellular proteins (Mcllwain et al, 2013).…”
Section: Statistical Analysis and Research Experiencementioning
confidence: 99%
“…As shown in Figure 1, accumulated data indicate that casticin was isolated from many plant species such as, namely Vitex agnus castus (Choudhary et al, 2009;Mesaik et al, 2009;Webster et al, 2011;Righeschi et al, 2012;Hogner et al, 2013), Daphne genkwa (Xie et al, 2011), Achillea millefolium (Haidara et al, 2006;Csupor-Loffler et al, 2009), Ficus microcarpa , Vitex rotundifolia (Ono et al, 2002;Hu et al, 2007b;Shen et al, 2009;Ye et al, 2010;Koh et al, 2011), Fructus viticis (Hu et al, 2007b;Guan et al, 2010;Chen et al, 2011b;Yang et al, 2011;Zeng et al, 2012;Zhou et al, 2013a), Vitex negundo (Diaz et al, 2003;Kunwar et al, 2010;Velpandian et al, 2013), Crataegus pinnatifida (Kao et al, 2005), Pavetta crassipes (Mali and Dhake, 2011), Nelsonia canescens, Butea frondosa Koen , Dalbergia odorifera (Mali and Dhake, 2011), Bryonia laciniosa (Aggarwal et al, 2011), Citrus unshu (Mali and Dhake, 2011;Nagoor et al, 2011), Centipeda minima (Mali and Dhake, 2011), Clausena excavate (Manosroi et al, 2005), Croton betulaster (de Sampaio e Spohr et al, 2010;Freitas et al, 2011), Dimorphandra mollis (Freitas et al, 2011), Artemisia abrotanum L. (Hernandez et al, 1999), Artemisia annua L …”
Section: Natural Sources Of Casticinmentioning
confidence: 99%
“…Casticin induced early or late apoptosis in a dose dependent manner. Sub-G1 accumulation is usually considered as an apoptotic death profile, this evidence is in sync with mode of cell death and characterized by a set of physiological phenomena, including mitotic catastrophe (Ono et al, 2002;Hu et al, 2007a;Hu et al, 2007b;Shen et al, 2009;Guan et al, 2010;Ye et al, 2010;Chen et al, 2011a;Koh et al, 2011;Zeng et al, 2012;Zhou et al, 2013a) Fructus viticis Chaste tree Mang Jing Zi Fruit Anticancer, inflammation (Hu et al, 2007b;Guan et al, 2010;Chen et al, 2011a;Zeng et al, 2012;Zhou et al, 2013a) Dimorphandra mollis --------Seeds vascular disorders; hypertension (Freitas et al, 2011) Artemisia abrotanum L.…”
Section: 9049 Molecular Mechanisms Of Casticin Action: An Update On mentioning
confidence: 99%